Clinical correlates of drug‐related dreams in opioid use disorder. Issue 1 (29th August 2021) - Ellis, Jennifer D.; Mayo, Jami L.; Finan, Patrick H.; Gamaldo, Charlene E.; Huhn, Andrew S.
Abstract: Background and Objectives: Drug‐related dreams are commonly reported by individuals in treatment for substance use disorders, which may be distressing. Existing evidence suggests that dream recollection may be influenced by clinically relevant phenomena, such as opioid use and withdrawal, general sleep disturbance, affective symptoms, and chronic pain. However, very few studies have explored drug‐related dreams among individuals who screened positive for opioid use disorder (OUD). Methods: Adults recruited from Amazon Mechanical Turk (MTurk) who screened positive for OUD ( N = 154) completed a questionnaire about drug‐related dreams, as well as measures assessing sleep, opioid use history, stress, anxiety, and chronic pain. χ 2 analyses, one‐way analysis of variance, and bivariate correlations, correcting for the false discovery rate, were used as appropriate to explore correlates of (1) recollecting a drug‐related dream, and (2) experiencing post‐dream craving and distress. Results: Individuals who recollected a past‐week drug‐related dream were more likely to report other recent sleep disturbances, including poorer sleep quality, greater insomnia symptoms, and a higher risk for sleep apnea. Post‐dream craving and distress were both associated with greater insomnia symptoms, poor sleep hygiene behaviors, and greater anxiety symptoms. Individuals who had ever experienced a drug‐related dream (recently, or in their lifetime) were more likely to report a history of severe withdrawal, overdose, and intravenous opioid use. Conclusion and Scientific Significance: Drug‐related dreams were common among individuals in the present sample and were related to other clinically relevant phenomena. Interventions that treat co‐occurring OUD, pain, sleep symptoms, and affective symptoms may improve overall well‐being in this population.